Chronic Lower Gastrointestinal Bleeding: Etiological Profile and Role of Colonoscopy among Children from sub‑Himalayan Ranges of North India - Sharma, Brij; Sharma, Rajesh; Bodh, Vishal; Sharma, Sudershan; Sood, Ashwani; Sharma, Rakesh; Sharma, Neetu (Journal of Digestive Endoscopy, 2018)
Background: Most patients with chronic lower gastrointestinal (GI) bleeding warrant endoscopic examination of the lower GI tract. This study was done to determine the etiological profile of chronic lower GI bleeding and the role of colonoscopy in its diagnosis, as well as the prognosis among children from sub‑Himalayan ranges of North India. Methods: In this study, we did a retrospective review of the clinical notes of children between 2 and 15 years of age who presented with chronic lower GI bleeding and underwent diagnostic and therapeutic colonoscopy in the Department of Gastroenterology, Indira Gandhi Medical College and Hospital, Shimla, from January 2012 to October 2017. Patient demographics, clinical features, and endoscopic and histopathological findings were recorded. Results: Of the total 57 patients reviewed, 22 (38.59%) were female and 35 (61.40%) were male, with a male‑to‑female ratio of 1.62:1.0. The highest incidence of lower GI bleeding was between the ages of 6 and 10 years (43.85%). The presenting symptoms were hematochezia in 50 (87.71%), bloody diarrhea in 5 (8.77%), and positive stool occult blood test in 2 (3.50%) patients. The most common accompanying symptom was constipation in 16 (28.07%), abdominal pain in 14 (24.56%), fever in 5 (8.77%), and weight loss in 5 (8.77%) patients. The most common colonoscopy finding was rectosigmoid polyps (36 cases, 63.15%) followed by internal hemorrhoids (9 cases, 15.78%), rectal ulcers (5 cases, 8.77%), findings suggestive of colitis of left colon (5 cases, 8.77%), and findings suggestive of ileocecal tuberculosis (2 cases, 3.50%). The most common histopathological finding was juvenile colorectal polyps (35 cases, 61.40%) followed by solitary rectal ulcer (5 cases, 8.77%), ulcerative colitis (5 cases, 8.77%), tuberculosis (2 cases, 3.50%), and Peutz–Jegher polyp (1 case, 1.75%). Conclusion: Juvenile colorectal polyps constitute the most common cause of chronic lower GI bleeding in children from sub‑Himalayan ranges of North India followed by hemorrhoids, solitary rectal ulcer, inflammatory bowel disease, and ileocolonic tuberculosis. Colonoscopy remains a useful and safe procedure in children for evaluation of lower GI bleeding both from the diagnostic and therapeutic points of view.
Keywords: Gastrointestinal; inflammatory bowel disease; solitary rectal ulcer syndrome; tuberculosis